Endocrine organ metastases from breast carcinoma. - de la Monte, S. M. (1984)
Breast carcinoma frequently metastasizes to endocrine organs, a behavior which may have prognostic or therapeutic relevance. Whether endocrine organ involvement represents a trophic influence on some carcinomas or is simply a "mass effect" of tumor dissemination is uncertain. To investigate this question, the authors reviewed the clinical and pathologic features of 187 subjects with metastatic breast carcinoma, all of whom had been subjected to complete autopsy at The Johns Hopkins Hospital. Metastases to primary endocrine organs, ie, the anterior pituitary, thyroid, parathyroid, or adrenal cortex, occurred in 57%, and metastases to secondary endocrine organs, ie, the pineal, posterior pituitary, thymus, adrenal medulla, or pancreas, occurred in 62% of patients. In general, patients with endocrine organ metastases were significantly younger and had significantly greater numbers of metastases and greater overall tumor burden than those without endocrine organ metastases (all P less than 0.001). There was no correlation between endocrine organ metastases and survival, therapy, histologic type of tumor, or grade of anaplasia or desmoplasia. Metastases to primary endocrine organs were correlated with one another and with metastases in secondary endocrine organs. Metastases in secondary endocrine organs were intercorrelated and also correlated with several nonendocrine organs, chiefly the heart, liver, and gut (all P less than 0.005). These findings indicate that metastases of breast carcinoma to endocrine organs occur in a setting of widely disseminated tumor. However, the observed correlations among metastatic sites suggest that the distributions are nonrandom; these distributions may reflect fundamental properties of some breast carcinomas with respect to hormone receptors, biologic behavior, or environmental growth requirements.